Early Detection of Breast Cancer in Adolescent Women at The Tapak Sunan Balekambang Condet Islamic Boarding School, Jakarta - Azzahroh, Putri; Silawati, Vivi (Rajaki of Tulip Medika Publisher, 2023)
Background: The existence of Higher Education has three main tasks, namely carrying out education and teaching, research, and community service. These three things constitute the Tridharma of Higher Education. In Indonesia, breast cancer is the second most common cancer suffered by women after oral/cervical cancer. Breast cancer generally attacks women who are over 40 years old. However, young women can get this cancer. To find early symptoms of breast cancer can be detected early by women themselves. Women can routinely perform the Breast Self-Examination (BSE) method by massaging and feeling around their breasts to find out whether or not there are lumps around the breasts. BSE is an effective way to detect breast cancer as early as possible. Objective: Carry out community service by conducting activities to teach breast self-examination (BSE) to young women. Method: This community service activity consists of counseling related to information on early detection of breast cancer and followed by a demonstration of breast self-examination (BSE) using the Breast Phantom tool. Result: Counseling and early detection of breast cancer was attended by 45 students of Madrasah Aliyah. Most students do not know about early detection of breast cancer and how to check BSE. After being given information about BSE, adolescents felt satisfied and committed to be able to carry out early detection of breast cancer. Conclusion: Community service activities have been carried out regarding information on early detection of breast cancer in young women.